Eco-Friendly Synthesis of Zinc Oxide Nanoparticles Using Parthenium hysterophorus Flower Extract for Antimicrobial and Antibiofilm Applications - Pallavi Bajirao Salunkhe; Gauri Mukesh Nagarkar; Avinash Ashok Survase; Geetanjali Vikas Utekar (The Bioscan, 2025)
Parthenium hysterophorus, a highly invasive weed from the Asteraceae family, is widely recognized for its detrimental ecological impact. However, recent studies highlight its significant antimicrobial and antibiofilm potential. This plant is rich in bioactive compounds, including alkaloids, flavonoids, phenols, terpenes, and pseudoguaianolides, which contribute to its therapeutic properties. Among its emerging applications, the green synthesis of nanoparticles using P. hysterophorus extracts has gained attention due to its eco-friendly and cost-effective nature. In particular, zinc oxide (ZnO) nanoparticles derived from P. hysterophorus exhibit remarkable antibacterial and antibiofilm activities. These nanoparticles effectively disrupt bacterial biofilms, a key factor in antimicrobial resistance (AMR), which is responsible for over a million deaths annually. Studies indicate that ZnO nanoparticles synthesized from P. hysterophorus extracts inhibit bacterial adhesion, impede biofilm formation, and display potent antibacterial properties against multidrug-resistant pathogens. Furthermore, green-synthesized ZnO nanoparticles leverage the plant’s rich phytochemical profile to enhance their efficacy while adhering to sustainable production principles. Although most research focuses on leaf-derived ZnO nanoparticles, the potential of flower-mediated synthesis remains largely unexplored. Expanding studies in this area could unveil novel antimicrobial strategies with enhanced specificity and potency. The integration of plant-based nanotechnology in biomedical applications presents a promising avenue for combating biofilm-associated infections and addressing global health challenges. Despite its medicinal potential, P. hysterophorus remains an aggressive invasive species, necessitating further research to harness its benefits while mitigating its ecological threats. Our significance of P. hysterophorus-derived nanoparticles in antimicrobial and antibiofilm applications, offering sustainable and effective solutions against drug-resistant infections.